If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -10 = x + -18 Reorder the terms: -10 + 5x = x + -18 Reorder the terms: -10 + 5x = -18 + x Solving -10 + 5x = -18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + 5x + -1x = -18 + x + -1x Combine like terms: 5x + -1x = 4x -10 + 4x = -18 + x + -1x Combine like terms: x + -1x = 0 -10 + 4x = -18 + 0 -10 + 4x = -18 Add '10' to each side of the equation. -10 + 10 + 4x = -18 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = -18 + 10 4x = -18 + 10 Combine like terms: -18 + 10 = -8 4x = -8 Divide each side by '4'. x = -2 Simplifying x = -2
| 18y+30=x | | 9x-10=38+3x | | 5x+5=x+33 | | 3x-6=-20 | | 27x+y=5 | | -9=4.9+k | | 2x+2=-3-2 | | x+4.7=5.8 | | 2x-10y=150 | | 2.7s=-29.7 | | 6+10=160 | | 6.6f=39.6 | | -3x=12x-4+1 | | 2.3=c-5.1 | | 21x-77=0 | | 5x+3y=65 | | 5s-25=2s+11 | | Cos(3x-30)=Sin(7x+50) | | 4-2cosx+5sinx=0 | | x-(-9)=7.9 | | 0.2xd+3=4 | | 4c+2p=45 | | 3x^2-13x+36=0 | | h=16t^2+40t+5 | | m^2+2m-575=0 | | 8x^4-20x^3-8x^2+20x=0 | | (a+3b)(2a-5b)= | | 9m+30=33 | | 6x(6x-5)-3(5-6x)= | | x^2+23-39=0 | | 16z^4-81z^4=0 | | a^2+6a+36=0 |